Ethnic differences and parental beliefs are important for overweight prevention and management in children: a cross-sectional study in the Netherlands - Kocken Paul L; Schönbeck Yvonne; Henneman Lidewij; Janssens A Cecile JW; Detmar Symone B (BMC, 2012)
Abstract Background The prevalence of obesity and overweight is highest among ethnic minority groups in Western countries. The objective of this study is to examine the contribution of ethnicity and beliefs of parents about overweight preventive behaviours to their child's outdoor play and snack intake, and to the parents' intention to monitor these behaviours. Methods A cross-sectional survey was conducted among parents of native Dutch children and children from a large minority population (Turks) at primary schools, sampled from Youth Health Care registers. Results Native Dutch parents observed more outdoor play and lower snack intake in their child and had stronger intentions to monitor these behaviours than parents of Turkish descent. In the multivariate analyses, the parents' attitude and social norm were the main contributing factors to the parental intention to monitor the child's outdoor play and snack intake. Parental perceived behavioural control contributed to the child's outdoor play and, in parents who perceived their child to be overweight, to snacking behaviour. The associations between parents' behavioural cognitions and overweight related preventive behaviours were not modified by ethnicity, except for perceived social norm. The relationship between social norm and intention to monitor outdoor play was stronger in Dutch parents than in Turkish parents. Conclusions As the overweight related preventive behaviours of both children and parents did differ between the native and ethnic minority populations of this study, it is advised that interventions pay attention to cultural aspects of the targeted population. Further research is recommended into parental behavioural cognitions regarding overweight prevention and management for different ethnicities.